The independent airport planning manual - Bradley, A. L. W. Alexandre L. W. (Oxford ; Philadelphia : Woodhead Pub., 2010)
This independent manual provides airport planners and architects with an essential planning guide and reference tool, based on the author's extensive experience in the field and involvement in developing best practice airline and airport industry guidelines. Chapters cover topics such as demand forecasting, masterplan development, terminal pier and satellite infrastructure, baggage handling, apron design and airport security. Provides airport planners and architects with an essential guide and reference tool, based on the author's extensive experienceDiscusses key airport planning issues including forecasting demand, planning and strategic objectives and airport securityOutlines important airport planning principles specified by IATA for masterplan development featuring evaluation techniques and independent development planning.
Machine generated contents note: 1. The brief to airport planners -- 1.1. Forecasts -- 1.2. Planning objectives and service levels -- 1.3. Development phasing strategy -- 1.4. Site constraints: physical and operational -- 1.5. Construction logistics -- 1.6. Airport security -- 1.7. Terminal and satellites/piers -- 1.8. Cargo buildings -- 1.9. General aviation facilities -- 1.10. Aircraft maintenance facilities -- 1.11. Airfield infrastructure -- 1.12. General support infrastructure -- 1.13. Ancillary facilities -- 1.14. Landscaping -- 1.15. Surface access -- 2. Outline airport planning principles -- 2.1. Industry standard planning approach -- 2.2. Masterplan evaluation techniques (evaluation criteria/pairwise/weighting) -- 2.3. Project drivers -- 2.4. Airport case study -- 3. Airport terminal and pier/satellite planning -- 3.1. Passenger segregation -- 3.2. Passenger experience: process flow diagrams and interactive models -- 3.3. Operational considerations: airport/airlines -- 3.4. Financial models -- 3.5. Retail design principles -- 3.6. Landside retail -- 3.7. Dwell periods -- 3.8. Airside retail: departures lounge/satellite/pier -- 3.9. Planning the size of terminal buildings -- 4. Airport baggage handling design -- 4.1. Categories of baggage handling systems -- 4.2. User requirements specification (URS) -- 4.3. Hold and hand baggage screening legislative requirements -- 4.4. Current and future baggage screening processes -- 4.5. Advances in baggage system automation -- 4.6. Advantages and disadvantages of the various hold baggage screening (HBS) processes and locations -- 4.7. Manual handling baggage hall design -- 5. Airport apron, runway and taxiway design -- 5.1. Function areas of the apron -- 5.2. Aircraft stands and multiaircraft ramping systems (MARS) -- 5.3. Passenger airbridges -- 5.4. Levels of passenger service -- 5.5. Low-cost carrier terminals versus full-service legacy terminals -- 5.6. Runway components -- 5.7. Restricted surface runways and taxiway ICAO Annex data -- 6. Design for airport security -- 6.1. Threats to aviation -- 6.2. Hijacking of aircraft -- 6.3. Sabotage of aircraft -- 6.4. Sabotage of airports -- 6.5. Legislation: international, European and domestic obligations -- 6.6. ICAO Annex 17 -- 6.7. Masterplan airport development considerations -- 6.8. Design options for terminals and piers -- 6.9. Impact of explosives on terminal infrastructure -- 6.10. Perimeter security -- 7. Case studies in airport planning -- 7.1. Introduction -- 7.2. Airport research report: Chisinau S.E. International Airport, Moldova -- 7.3. Airport research report: Cologne Bonn Airport, Germany -- 7.4. Airport research report: Adelaide Airport, Australia -- 7.5. Airport research report: low-cost bespoke terminal, Luton Airport, UK -- 7.6. Airport research report: low-cost terminal, Frankfurt Hahn Airport, Germany.
Includes index.
Keywords: Airports -- Planning -- Handbooks, manuals, etc; TRANSPORTATION / Ships & Shipbuilding / Pictorial; Airports -- Planning